A STUDY OF CLINICAL AND PARACLINICAL FEATURES AND MODE OF DELIVERY OF PRETERM LABOR IN PREGNANT WOMEN (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and paraclinical characteristics and evaluate the methods of pregnancy termination in pregnant women with preterm labor at Binh Duong General Hospital from July 2025 to February 2026.Subjects and methods: A prospective, descriptive cross-sectional study with analysis. Results: The average age of pregnant women in the study group was 26.14 ± 8.06 years, with the youngest being 15 years and the oldest 42 years. The majority of pregnant women lived in rural areas (96.67%), and had one child (57.78%). 25.56% of pregnant women worked more than 8 hours/day; and 35.55% had a BMI ≥ 23 kg/m2. The average gestational age at admission was 34.14 ± 2.45 weeks, with the youngest being 28 weeks and the oldest 36 weeks and 6 days. 48.89% of pregnant women delivered vaginally, and the rates of cesarean section and vaginal delivery were similar in both gestational age groups. The rate of admission to the neonatal intensive care unit was high (85.55%).Conclusions: The majority of preterm births occurred at a gestational age of ≥ 34 weeks.
Keywords: Preterm birth, cesarean section, BMI.